Bioacoustics and morphology of a new bush-cricket species of the genus Isophya (Orthoptera: Phaneropterinae) from Turkey - Sevgi̇li̇ Hasan (Zootaxa, 2018)
A new interesting species of the genus Isophya, I. horon sp. n., is described from Northeastern part of Turkey. The new species can clearly be distinguished from the closely related species by the calling song of male, and morphology. Morphologically, the shapes of the pronotum, tegmina, male cerci and ovipositor are distrinctive. The morphology, song structure and distribution clearly indicate that this new species is a member of the I. zernovi species-group. Additionally, some preliminary data on the male calling songs of closely related species (I. zernovi, I. karadenizensis and I. autumnalis) are also given. In addition, the preliminary data related to spermatophore characteristics (spermatophylax and ampulla weights) and sperm number of the new species are provided.